Language Interference Among EFL Students: A Case Study of Thai Students at Muhammadiyah Kendari University - Nurshiyam Hanrolan; Tambunan Tambunan; Nurnia Nurnia (Halu Oleo University, 2023)
This study analyzed the English writing of Thai EFL students at Muhammadiyah Kendari University, focusing on two main questions: (1) What writing errors do Thai EFL students make in their English paragraphs? (2) How does their first language interfere with their performance in writing English paragraphs? A descriptive qualitative method was used to identify writing errors and describe first language interference. Errors in punctuation, tenses, spelling, agreement, prepositions, finite verbs, and articles were highlighted and coded in the writing samples. The findings revealed significant errors in the students' writing, many of which were due to first language interference. These errors were primarily grammatical and phonological, resulting from differences between Thai and English grammar rules and language forms. This study underscores the challenges Thai EFL students face in writing English paragraphs and emphasizes the need to address first language interference to enhance writing proficiency. The findings can contribute to developing tailored teaching strategies and curriculum designs for Thai EFL learners.